Ultimate Typescript Handbook: Build, Scale and Maintain Modern Web Applications with Typescript - Wellman, Dan (Orange Education PVT Ltd, 2023)
This book provides a comprehensive guide to TypeScript, a programming language that extends JavaScript with powerful features like static typing, classes, and interfaces. The book is divided into thirteen chapters that cover everything from setting up a development environment to building an Angular app with TypeScript. We start with an introduction to TypeScript and its benefits and go on to explain how TypeScript can help developers write more maintainable, scalable code and catch errors before they make it to production. The book then dives into more technical topics like basic type annotations, using the TypeScript compiler, advanced features like enums and interfaces, and manipulating types. The book then discusses chapters on classes and control flow analysis that are particularly helpful for developers looking to build more complex applications. The book teaches by example, with numerous code examples that illustrate the main concepts and approaches towards writing TypeScript programs and codes, and finishes with a comprehensive practical example that shows step-by-step development of a modern web application using TypeScript and Angular.